Implementation of an e-Voting System for Electing the Student Executive Board Chair Using QR Codes: Implementasi Sistem Pemungutan Suara Elektronik (e-Voting) untuk Pemilihan Ketua Badan Eksekutif Mahasiswa Menggunakan Kode QR - Sintya Devi Januari; Darsanto; Muh Pauzan (NUANSA INFORMATIKA, 2026)
Information technology plays a crucial role in supporting all campus activities, including student organizations, which serve as a forum for developing leadership, interests, and talents. One of the main activities of this organization is the election of the Student Executive Board (BEM) chairman. However, elections are still conducted manually using paper ballots, which is time-consuming, inefficient, and prone to fraud. This research aims to design an e-Voting system based on QR Code technology using the Dynamic System Development Method (DSDM) as a system design solution that can ensure compliance with needs and changes during the development process. In this study, the resulting e-Voting system was analyzed using the ISO 9241-11 standard. Parameters measured in the ISO 9241-11 standard include effectiveness, efficiency, and user satisfaction. The results of the analysis show that the e-Voting system achieved 95% effectiveness, 94% efficiency and user satisfaction got a score of 73 as measured based on the System Usability Scale (SUS) included in the category above the eligibility standard, namely 68, so that the score of 73 got an adjective scale as Good, with a grade B, at the Acceptable level and included in the Passive category on the NPS scale. This study shows that the QR Code-based e-Voting system can be a reliable, efficient alternative and increase transparency and a satisfying experience for voters in the BEM chairman election process